Power supply of start-up of the engine internal combustion of the car - A. G. Markin; B. V. Zhuravsk; A. P. Zhigadlo (Вестник СибАДИ, 2017)
The article analyzes the reasons of the complicated start-up automotive internal combustion engines in the conditions of low negative temperatures. It is shown that decisive impact on the energy system has a start value of the internal resistance of the battery. They say that one of the main causes of increased internal resistance of the battery during operation of the vehicle is its low degree of charge. The influence of the modes of operation of the vehicle to charge the battery. The description of the operation principles of the proposed intelligent energy supply system of the vehicle.